Application of the condensed protocol for the NIA‐AA guidelines for the neuropathological assessment of Alzheimer's disease in an academic clinical practice. Issue 3 (22nd November 2017) - Bharadwaj, Rajnish; Cimino, Patrick J; Flanagan, Margaret E; Latimer, Caitlin S; Gonzalez‐Cuyar, Luis F; Juric‐Sekhar, Gordana; Montine, Thomas J; Marshall, Desiree A; Keene, C. Dirk
Abstract : Aims: In response to concerns regarding resource expenditures required to implement fully the 2012 National Institute on Aging and the Alzheimer's Association (NIA‐AA) Sponsored Guidelines for the neuropathological assessment of Alzheimer's disease (AD), we previously developed a sensitive and cost‐reducing condensed protocol (CP) at the University of Washington (UW) Alzheimer's Disease Research Center (ADRC) that consolidated the recommended NIA‐AA protocol into fewer cassettes requiring fewer immunohistochemical stains. The CP was not designed to replace NIA‐AA protocols, but instead to make the NIA‐AA criteria accessible to clinical and forensic neuropathology practices where resources limit full implementation of NIA‐AA guidelines. Methods and results: In this regard, we developed practical criteria to instigate CP sampling and immunostaining, and applied these criteria in an academic clinical neuropathological practice. During the course of 1 year, 73 cases were sampled using the CP; of those, 53 (72.6%) contained histological features that prompted CP work‐up. We found that the CP resulted in increased identification of AD and Lewy body disease neuropathological changes from what was expected using a clinical history‐driven work‐up alone, while saving approximately $900 per case. Conclusions: This study demonstrates the feasibility and cost‐savings of the CP applied to a clinical autopsy practice, and highlights potentially unrecognised neurodegenerative disease processes in the general ageing community.